POTENSI PEMANFAATAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA PEMBELAJARAN DALAM PEMBELAJARAN DARING - Nurin Salma Ramdani; Hafsah Nugraha; Angga Hadiapurwa (Akademika : Jurnal Teknologi Pendidikan, 2021)
The development of Tiktok learning media is in line with the current digital era. This gives rise to social media that can be a learning medium because social media attracts attention and is close to the millennial generation who are indeed attached to the digital world. One of the social media that is currently popular is the Tiktok application. Tiktok can be an interesting and fun learning medium. The use of the Tiktok application as a learning medium is expected to help students and educators in learning. Therefore, this study aims to show that Tiktok social media can be an alternative and interactive learning media in online learning. The method used is a literature study by analyzing fourteen articles relevant to the development of TikTok as a learning medium. The results of the study show that the use of Tiktok social media as a learning medium can increase the activeness and creativity of students in the online learning process. Students can freely express their creativity through Tiktok with various features, thus making Tiktok as an effective learning medium in creating interactive online learning. This research is influential in making Tiktok social media as an interactive learning media for educators and students in online learning